2020
DOI: 10.3390/drones4010006
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Height Characteristics of Sagebrush (Artemisia sp.) Using Imagery Derived from Small Unmanned Aerial Systems (sUAS)

Abstract: In situ measurements of sagebrush have traditionally been expensive and time consuming. Currently, improvements in small Unmanned Aerial Systems (sUAS) technology can be used to quantify sagebrush morphology and community structure with high resolution imagery on western rangelands, especially in sensitive habitat of the Greater sage-grouse (Centrocercus urophasianus). The emergence of photogrammetry algorithms to generate 3D point clouds from true color imagery can potentially increase the efficiency and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In this study, we did not include structural data as computing the structure‐for‐motion point cloud can be computational and time intensive, which may be a limitation for user groups who wish to apply these drone imagery protocols. Nevertheless, UAS‐derived structural measurements can accurately represent plant height and aboveground biomass in dryland ecosystems (Cunliffe et al, 2016; Howell et al, 2020) and would likely improve classification accuracy of PFTs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not include structural data as computing the structure‐for‐motion point cloud can be computational and time intensive, which may be a limitation for user groups who wish to apply these drone imagery protocols. Nevertheless, UAS‐derived structural measurements can accurately represent plant height and aboveground biomass in dryland ecosystems (Cunliffe et al, 2016; Howell et al, 2020) and would likely improve classification accuracy of PFTs.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, in the agricultural context, it was reported that the error of the plant height measured using drones is 88.39 mm [31] or approximately 100 mm [32], and further improvement is required. From the rst experiment, it was con rmed that high-precision growth measurement of plants was possible using the proposed method.…”
Section: Second Experimentsmentioning
confidence: 99%
“…Remote sensing with a xed camera enables high-precision measurement of plant height [28,29] ; however, the accuracy of measurement decreases when the position and attitude of the camera, such as drone measurement, need to be speci ed. It was reported that the error in the plant height measured using drones is 88.39 mm [30] or approximately 100 mm [31] , and further improvement in accuracy is required.…”
Section: Limitations Of Sfm (Agricultural Context)mentioning
confidence: 99%
“…Additionally, the capabilities and speed of computational SfM data processing are steadily increasing. This collection method has facilitated advances for many scientific investigations, including object height detection [17,18], geomorphic change [19,20], geologic change [3], glacial change [21], and cliff stability [22].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the recent research in UAS-based topographic change measurement methodologies has been focused on increasing the accuracy [23][24][25] and efficiency [26][27][28] of digital elevation model (DEM) production from SfM photogrammetry. Some methodological studies have focused on reducing the above ground level (AGL) flight height of the UAS, to achieve a lower ground sample distance (GSD; the real-world space contained within a pixel of data) and therefore increase accuracy [17,29]. Other studies have focused on the methods for the optimization of survey control alignment [26,30,31].…”
Section: Introductionmentioning
confidence: 99%